The Implementation of Digital Technology in Online Project-Based Learning during Pandemic: EFL Students’ Perspectives - Gallis Nawang Ginusti (J-SHMIC : Journal of English for Academic, 2023)
Integrating technology and digital media into project-based learning (PBL) is the best strategy for addressing the challenges of the English classroom in the digital age as well as providing an online learning alternative during the Covid-19 pandemic. This is a case study that investigates the utilization of technology in PBL and the benefits and drawbacks experienced by students. To conduct the case study, open-ended questionnaires were distributed to 118 students to get a wide range of perspectives on the implementation. The findings indicated that a numerous digital technology and tools were used to succeed in PBL learning ranging from LMS, video conferencing platforms, virtual whiteboard apps, chat and messaging, messaging and collaboration apps, Web 2.0, word processing, presentation software, graphic design or drawing tools, and photo editors. They concurred that the technology-mediated PBL was beneficial because it facilitated remote learning, offered online discussion/collaboration and feedback, was accessible and flexible, encourage creativity and allowed students to explore new knowledge as well as knowledge to produce a digital product, and also enhanced technological literacy. However, there were still significant obstacles existed especially the issues of internet connectivity and technology operation. In addition, they also had difficulties in articulating ideas using the technology and managing their time to complete the project.